0.13x+0.6(x-3)=0.01(2x-5)

Simple and best practice solution for 0.13x+0.6(x-3)=0.01(2x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.13x+0.6(x-3)=0.01(2x-5) equation:


Simplifying
0.13x + 0.6(x + -3) = 0.01(2x + -5)

Reorder the terms:
0.13x + 0.6(-3 + x) = 0.01(2x + -5)
0.13x + (-3 * 0.6 + x * 0.6) = 0.01(2x + -5)
0.13x + (-1.8 + 0.6x) = 0.01(2x + -5)

Reorder the terms:
-1.8 + 0.13x + 0.6x = 0.01(2x + -5)

Combine like terms: 0.13x + 0.6x = 0.73x
-1.8 + 0.73x = 0.01(2x + -5)

Reorder the terms:
-1.8 + 0.73x = 0.01(-5 + 2x)
-1.8 + 0.73x = (-5 * 0.01 + 2x * 0.01)
-1.8 + 0.73x = (-0.05 + 0.02x)

Solving
-1.8 + 0.73x = -0.05 + 0.02x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.02x' to each side of the equation.
-1.8 + 0.73x + -0.02x = -0.05 + 0.02x + -0.02x

Combine like terms: 0.73x + -0.02x = 0.71x
-1.8 + 0.71x = -0.05 + 0.02x + -0.02x

Combine like terms: 0.02x + -0.02x = 0.00
-1.8 + 0.71x = -0.05 + 0.00
-1.8 + 0.71x = -0.05

Add '1.8' to each side of the equation.
-1.8 + 1.8 + 0.71x = -0.05 + 1.8

Combine like terms: -1.8 + 1.8 = 0.0
0.0 + 0.71x = -0.05 + 1.8
0.71x = -0.05 + 1.8

Combine like terms: -0.05 + 1.8 = 1.75
0.71x = 1.75

Divide each side by '0.71'.
x = 2.464788732

Simplifying
x = 2.464788732

See similar equations:

| 8(s+3)=73 | | -6x-15x+36=0 | | 8(-44)+5(5)= | | 1856/3-6*x*631(65-44)=1271477.33333333 | | z-24=-99 | | 1856/3-6*x*631(65-44)=1271477.3333333 | | (4+-5)(3s+1)= | | 3(1.2d-1)+3.6=4.2 | | 0.08(x+6)=0.04(2x+9)+0.12 | | 13u-5u=72 | | 5x+2x=9 | | 128=5n-6+3 | | -4.2+31.5=66.1 | | f(x)=4x^2+9 | | -75+11x=37+7x | | 8y+12=-8y-12 | | 1856/3-6*16*631(65-44)= | | 5(-9)+4(-2)= | | 8x+25=-17 | | 6+x*2=5 | | -179+11x=51+x | | (0x^4)-(5x^2)= | | 12x-59=6x+61 | | 10+3y=-2 | | -80h^3+200h^2y-125hy^2= | | 3d-12d=10 | | -5(x-1)=6(x-4) | | 6y+-4y=-4 | | (X-5)2+(y-7)2=64 | | 3.8x+12.1=9.3 | | 2x+24=-6x | | 3x-40+x-y=180 |

Equations solver categories